Introduction to Radiation Protection Practical Knowledge for Handling Radioactive Sources - Grupen, Claus; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The book presents an accessible account of the sources of ionising radiation and the methods of radiation protection. The basics of nuclear physics which are directly related to radiation protection are briefly discussed. The book describes the units of radiation protection, the measurement techniques, biological effects of radiation, environmental radiation, and many applications of radiation. For each chapter there is a problem section with full solutions. A detailed glossary and many useful information in appendixes complete the book. The author has addressed the issue of internationality to make sure that the text and, in particular, the complicated regulations can be easily interpreted not only in Europe and the United States but also in other countries. The subject of radiation protection requires a certain amount of mathematics. For those who have forgotten the basic rules of calculus a short refresher course in the form of a mathematical appendix is added.
Units of Radiation Protection -- Basic Nuclear Physics -- Interaction of Ionizing Radiation with Matter -- Detectors for Radiation Protection -- International Safety Standards for Radiation Protection -- Organization of Radiation Protection -- Practical Safety Measures1 -- Radiation Sources -- X Rays and X-Ray Regulations -- Environmental Radioactivity -- Nuclear Power Plants -- Biological Effects of Ionizing Radiation -- Radiation Accidents -- Non-Ionizing Radiation -- Solutions to the Problems -- Written Test on Radiation Protection -- Radiation-Protection Glossary1.
Keywords: Physics; Radiology, Medical; Nuclear medicine; Radiotherapy; Physics; Biophysics and Biological Physics; Radiotherapy; Imaging / Radiology; Particle and Nuclear Physics; Measurement Science and Instrumentation; Nuclear Medicine